Digitalization in providing transparency in the management of the public finance and asset (Economics and region, 2020)
We propose options for resolving the conflict situation regarding the conscious use of the state database (Unified database of valuation reports with the module of electronic valuation of property value) as a source of undue benefit to four authorized electronic sites, namely expanding the range of accredited e-sites and reducing the cost of services to reason or the introduction of direct access to the Unified Database of valuation reports and the principle of free of charge for the service of entering or using the property valuation database. The situation of conditionality of access to information in the sphere of management of state property objects (the Unified register of state property objects), which is evidence of its closedness (not on the grounds of strategic importance, secrecy, etc.), limitation of opportunities to increase the efficiency of temporarily unused state assets in the production of different assets is revealed sharing mechanisms, including rental mechanisms. The directions of development of digitalization of administrative services and transparency in the sphere of management of state assets are outlined. The need to change the paradigm of government asset management is emphasized. In view of the public demand for transparency of public administration, this requires quality regulatory regulation of digital transformation, development of secure digital infrastructure, active public-private partnerships to create technological platforms, and change of general approaches to the public asset management system, which is the direction of further scientific exploration.
Keywords: digitalization; public finance; assets; management; business